Nocturnal Hypoxemia Severity and Renin–Angiotensin System Activity in Obstructive Sleep Apnea - Zalucky, Ann A.; Nicholl, David D. M.; Hanly, Patrick J.; Poulin, Marc J.; Turin, Tanvir C.; Walji, Shahebina; Handley, George B.; Raneri, Jill K.; Sola, Darlene Y.; Ahmed, Sofia B. (American journal of respiratory and critical care medicine, 2015)
Obstructive sleep apnea (OSA) and nocturnal hypoxemia are associated with chronic kidney disease and up-regulation of the renin-angiotensin system (RAS), which is deleterious to renal function. The extent to which the magnitude of RAS activation is influenced by the severity of nocturnal hypoxemia and comorbid obesity has not been determined. To determine the association between the severity of nocturnal hypoxemia and RAS activity and whether this is independent of obesity in patients with OSA. Effective renal plasma flow (ERPF) response to angiotensin II (AngII) challenge, a marker of renal RAS activity, was measured by paraaminohippurate clearance technique in 31 OSA subjects (respiratory disturbance index, 51 ± 25 h(-1)), stratified according to nocturnal hypoxemia status (mean nocturnal SaO2, ≥90% [moderate hypoxemia] or <90% [severe hypoxemia]) and 13 obese control subjects. Compared with control subjects, OSA subjects demonstrated decreased renovascular sensitivity (ERPF, -153 ± 79 vs. -283 ± 31 ml/min; P = 0.004) (filtration fraction, 5.4 ± 3.8 vs. 7.1 ± 2.6%; P = 0.0025) in response to 60 minutes of AngII challenge (mean ± SD; all P values OSA vs. control). The fall in ERPF in response to AngII was less in patients with severe hypoxemia compared with those with moderate hypoxemia (P = 0.001) and obese control subjects after 30 minutes (P < 0.001) and 60 minutes (P < 0.001) of AngII challenge, reflecting more augmented renal RAS activity. Severity of hypoxemia was not associated with the blood pressure or the systemic circulating RAS component response to AngII. The severity of nocturnal hypoxemia influences the magnitude of renal, but not the systemic, RAS activation independently of obesity in patients with OSA.